Neurological risks and benefits of cytokine‐based treatments in coronavirus disease 2019: from preclinical to clinical evidence. (12th March 2021) - Pignataro, Giuseppe; Cataldi, Mauro; Taglialatela, Maurizio
Abstract : Immunodeficiency and hyperinflammation are responsible for the most frequent and life‐threatening forms of coronavirus disease 2019 (COVID‐19). Therefore, cytokine‐based treatments targeting immuno‐inflammatory mechanisms are currently undergoing clinical scrutiny in COVID‐19‐affected patients. In addition, COVID‐19 patients also exhibit a wide range of neurological manifestations (neuro‐COVID), which may also benefit from cytokine‐based treatments. In fact, such drugs have shown some clinical efficacy also in neuroinflammatory diseases. On the other hand, anti‐cytokine drugs are endowed with significant neurological risks, mainly attributable to their immunodepressant effects. Therefore, the aim of the present manuscript is to briefly describe the role of specific cytokines in neuroinflammation, to summarize the efficacy in preclinical models of neuroinflammatory diseases of drugs targeting these cytokines and to review the clinical data regarding the neurological effects of these drugs currently being investigated against COVID‐19, in order to raise awareness about their potentially beneficial and/or detrimental neurological consequences. LINKED ARTICLES: This article is part of a themed issue on The second wave: are we any closer to efficacious pharmacotherapy for COVID 19? (BJP 75th Anniversary). To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v179.10/issuetoc